NP program efforts promoting transition to rural practice. Issue 10 (October 2020) - Kaplan, Louise; Pollack, Samantha W.; Skillman, Susan M.; Patterson, Davis G.
Abstract : Abstract: This article presents the results of a study that identifies, describes, and compares the approaches of rural-oriented NP education programs to facilitate the NP transition from education to practice in rural settings. Preparing NP students effectively during their education may be key to their success in rural practice. Abstract : This article presents the results of a study that identifies, describes, and compares the approaches of rural-oriented NP education programs to facilitate the NP transition from education to practice in rural settings. Preparing NP students effectively during their education may be key to their success in rural practice.